The intended Meanings of Definiteness and indefiniteness for the expressions in Holy Quran - Hassan, Faisal M.; Mustafa, Idris S.; Ismail, Hazem Th. (Humanities Journal of University of Zakho, 2013)
The research aims at explaining the signification of definiteness and indefiniteness in the Holy Quran and disclosing the colorfulness of style between the two terms. It also endeavors to study them, and explain their conceptual meanings, their coinage, and the difference of their contexts in The Holy Quran. The word occurs without a definite article in a certain position and with it in another position according to its context. Definiteness and indefiniteness are considered stylistic aspects that give flexibility to the coinage and trackmen of the vocabulary in the sentence.